DESIGN AND IMPLEMENTATION OF THREE LEVEL H-BRIDGE INVERTER BASED D-STATCOM - Deniz, Erkan; Coteli, Resul; Dandil, Besir; Tuncer, Servet (Gazi Univ, Fac Engineering Architecture, 2011)
Distribution Static Synchronous Compensator (D-STATCOM) is an inverter based custom power devices used to improve power quality problems in distribution systems. In this paper, design of inverter, measurement, protection and dead-time circuits needed to build experimental setup of three-level H-bridge inverter based D-STATCOM is explained in detail. In addition, selection of passive elements which are coupling inductance and dc-link capacitor being important for dynamic response of compensator is given. In experimental study, DS1103 controller card from dSPACE firm is used to transfer data between D-STATCOM and computer. D-STATCOM's ability for reactive power support is tested in experimental setup by changing of i(qref) as on-line and some results are given.
Keywords: D-STATCOM; experimental setup; three-level H-bridge inverter; DS1103